2015
DOI: 10.1186/s40064-015-1127-z
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Tetranychus urticae Koch to an ethanol extract of Cnidoscolus aconitifolius leaves under laboratory conditions

Abstract: One of the main pests of commercial rose crops in Colombia is the phytophagous mite Tetranychus urticae Koch. To manage this pest, synthetic chemicals have traditionally been used, some of which are well known to be potentially toxic to the environment and humans. Therefore, alternative strategies for pest management in greenhouse crops have been developed in recent years, including biological control with natural enemies such as parasitoids, predators and entomopathogenic microorganisms as well as chemical co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…The results shown in Table 3 indicated that ethanol extracts of H. niger and H. calycinum caused a reduction in the number of eggs laid per female. This is consistent with the results established by Numa et al [40] who reported that application of plant extracts may affect the oviposition of T. urticae females. It was revealed that the number of eggs laid per female decreases when an increasing concentration of a plant extract was applied [41,42].…”
Section: Effect On Reproductive Capacitysupporting
confidence: 93%
“…The results shown in Table 3 indicated that ethanol extracts of H. niger and H. calycinum caused a reduction in the number of eggs laid per female. This is consistent with the results established by Numa et al [40] who reported that application of plant extracts may affect the oviposition of T. urticae females. It was revealed that the number of eggs laid per female decreases when an increasing concentration of a plant extract was applied [41,42].…”
Section: Effect On Reproductive Capacitysupporting
confidence: 93%
“…The solvent was removed by rotary evaporation to dryness and the resulting material dried completely in an oven at 25°C. Numa et al (2015) mention that to prepare the soluble extract in ethanol, the C. aconitifolius leaf was dried, ground and macerated for 7 days in a solution of 96% ethanol, changing the solvent daily.…”
Section: Aconitifoliusmentioning
confidence: 99%
“…bras., Brasília, v.52, n.10, p.841-848, out. 2017 DOI: 10.1590/S0100-204X2017001000003 on the mortality of the adult females of Tetranychus urticae (Numa et al, 2015); and the extracts and oils of C. phyllacanthus exerting a larvicidal effect on the control of Aedes aegypti (Candido et al, 2013). The ethanolic leaf and root extracts and the aqueous root extract caused the larval phase of the cabbage caterpillar to be prolonged, in comparison with the other treatments that also showed differences from one another (Table 2).…”
Section: Resultsmentioning
confidence: 99%